Iron-based low-cost magnetocaloric materials for near room temperature magnetic cooling - Sharma, Vinay Kumar (2019)
Magnetic cooling relies on magnetocaloric materials (MCM). It is an emerging energy efficient, “green” thermal management technology which has the potential to replace conventional gas-compressor based cooling systems. Current research on MCM aims at developing low-cost, environmentally friendly materials which can be manufactured by simple processes and exhibit superior magnetocaloric effect (MCE) near room temperature. Many materials have been developed over the years which exhibit high MCE, however they suffer from disadvantages such as high cost of rare earth (RE) elements, low corrosion and oxidation resistance, tedious synthesis routes, strategic limitations etc. Hence, good performance and readily available MCM with high corrosion resistance and established manufacturing technology are urgently needed for cooling applications near room temperature.